Mac mini Hacks & Mods for Dummies - Rizzo, John (Wiley Publishing, 2011)
Starting at $499, the diminutive Mac mini-2.5 inches tall, 6.5 inches wide, and 2.9 pounds-is expected to become Apple's bestselling computer, with projected shipments of 100,000 units a month This book offers several projects-some easy, some more challenging-to help people tweak, modify, and transform a Mac mini Modest modifications include creating a Mac mini home theater, an appliance controller, and a travel kit; other more complex (but very cool!) mods require wielding a soldering iron Offers detailed, illustrated step-by-step instructions-including how to open the Mac mini, keep track of pieces, and avoid damage-that enable even novice tinkerers to complete the projects